Phylogenomics and multigene phylogenies decipher two new cryptic marine algae from California, Gelidium gabrielsonii and G. kathyanniae (Gelidiales, Rhodophyta). Issue 1 (26th November 2018) - Boo, Ga Hun; Hughey, Jeffery R.
Abstract : Molecular surveys are leading to the discovery of many new cryptic species of marine algae. This is particularly true for red algal intertidal species, which exhibit a high degree of morphological convergence. DNA sequencing of recent collections of Gelidium along the coast of California, USA, identified two morphologically similar entities that differed in DNA sequence from existing species. To characterize the two new species of Gelidium and to determine their evolutionary relationships to other known taxa, phylogenomic, multigene analyses, and morphological observations were performed. Three complete mitogenomes and five plastid genomes were deciphered, including those from the new species candidates and the type materials of two closely related congeners. The mitogenomes contained 45 genes and had similar lengths (24, 963–24, 964 bp). The plastid genomes contained 232 genes and were roughly similar in size (175, 499–177, 099 bp). The organellar genomes showed a high level of gene synteny. The two Gelidium species are diminutive, turf‐forming, and superficially resemble several long established species from the Pacific Ocean. The phylogenomic analysis, multigene phylogeny, and morphological evidence confirms the recognition and naming of two new species, describe herein as G. gabrielsonii and G. kathyanniae . On the basis of the monophyly of G. coulteri, G. gabrielsonii, G. galapagense, and G. kathyanniae, we suggest that this lineage likely evolved in California. Organellar genomes provide a powerful tool for discovering cryptic intertidal species and they continue to improve our understanding of the evolutionary biology of red algae and the systematics of the Gelidiales.